Dividend policy and the nature of cash flows of selected companies listed on the Frankfurt Stock Exchange - Dada, Anna (Polityka dywidend a charakter przepływów pieniężnych wybranych spółek notowanych na Giełdzie Papierów Wartościowych we Frankfurcie, 2021)
The main purpose of the article was to investigate whether there are joint-stock companies listed on the FSE between 2000-2017 that paid regular dividends. The sample was divided into dividend companies and other companies. A subsidiary objective was to compare the dividend companies and other companies concerning the direction of their cash flows (positive/negative). Based on the conducted research, it should be stated that dividend companies had on average higher DPS than other companies. The conducted research shows that the percentage of dividend companies in variants 1-4 among the models of eight cases based on selected information on cash flows is greater than that of other companies. The application value is related to recommendations regarding the attractiveness of investing in dividend companies. These conclusions may also be useful for companies listed on other exchanges, e.g. the GPW. The dividend payment policy should be supported by rational cash flow management.
Financial Sciences. Nauki o Finansach, 2021, vol. 26, no. 2, s. 30-44
Keywords: dividend policy; cash flow; Franfurkt Stock Exchange; polityka dywidend; przepływy pieniężne; Giełda Papierów Wartościowych we Frankfurcie